2013
DOI: 10.1126/science.1231197
|View full text |Cite
|
Sign up to set email alerts
|

Translational Repression and eIF4A2 Activity Are Critical for MicroRNA-Mediated Gene Regulation

Abstract: MicroRNAs (miRNAs) control gene expression through both translational repression and degradation of target messenger RNAs (mRNAs). However, the interplay between these processes and the precise molecular mechanisms involved remain unclear. Here, we show that translational inhibition is the primary event required for mRNA degradation. Translational inhibition depends on miRNAs impairing the function of the eIF4F initiation complex. We define the RNA helicase eIF4A2 as the key factor of eIF4F through which miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
321
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 293 publications
(350 citation statements)
references
References 38 publications
24
321
2
3
Order By: Relevance
“…Several studies reported that miRNAs silence gene expression by targeting eIF4A and interfering with ribosome scanning (Meijer et al , 2013; Ricci et al , 2013; Fukao et al , 2014; Fukaya et al , 2014). However, there were considerable disagreements between these studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies reported that miRNAs silence gene expression by targeting eIF4A and interfering with ribosome scanning (Meijer et al , 2013; Ricci et al , 2013; Fukao et al , 2014; Fukaya et al , 2014). However, there were considerable disagreements between these studies.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we generated a reporter containing a 5′‐UTR consisting of 18 CAA repeats, which is unlikely to adopt secondary structures, and its translation is thought to be independent of eIF4A (Meijer et al , 2013). This 5′‐UTR was also shown to confer resistance to silencing (Meijer et al , 2013). Unexpectedly, translation of this reporter was partially inhibited by silvestrol (Figs 4A and EV3H).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations